Heterogeneity of Phenotype and Function Reflects the Multistage Development of T Follicular Helper Cells - David Gray; Marta Trüb; Tom A. Barr; Vicky L. Morrison; Sheila Brown; Stefano Caserta; Jordan Rixon; Alasdair Ivens (Frontiers in Immunology, 2017)
T follicular helper cells (Tfh) provide crucial signals for germinal center (GC) formation, but Tfh populations are heterogeneous. While PD1hi Tfh are important in the GC response, the function of the PD1lo Tfh-like subset is unknown. We show that these cells, like the PD1hi GC–Tfh, depend upon B cells; however, their entry to follicles is independent of CXCR5 or cognate interactions with B cells. The differentiation into PD1hi Tfh is dependent on MHC class II interactions with B cells and requires CXCR5. Our data suggest a Tfh differentiation pathway that is initially B cell-independent, then dependent on non-cognate B cell interactions, and finally following cognate interaction with B cells and CXCR5-ligands allows the formation of GC–Tfh. The PD1lo Tfh-like cells make early cytokine responses and may represent precursors of CD4 memory cells.